2013
DOI: 10.9790/0853-0437376
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen And Progesterone Receptors In Dysfunctional Uterine Bleeding

Abstract: Objective:To analyze estrogen and progesterone receptors (ER, PR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…[9] In our study we studied ER and PR expression in endometrial glands and stroma separately as well as a total expression. We found that the maximum ER and PR expression was noted in the glandular epithelium, except for PR expression in the secretory phase which was more in the stromal cells than glandular epithelial cells, a finding supported by Press et al [12] Expression of these receptors was observed to be absent from vascular smooth muscle and endothelial cells in both endometrium and myometrium in the present study; also reported by Chakraborty et al, Press et al and Snijders et al [5,12,13] It was also noted during our study that the method of endometrial sampling did not affect the demonstration of ER and PR expression, a finding corroborated by study of Garcia et al [14] Antigen retrieval for ER is considered to be difficult as stated by Shet T et al, [15] but we did not find any significant discrepancy in the staining intensity for ER and PR. Although, staining for PR was more crisp and brighter than that for ER in most of our cases, which can be easily explained by the quantitative data from steroid-binding assays indicating that the content of PR in femtomoles per milligram cytosol protein is greater than ER.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[9] In our study we studied ER and PR expression in endometrial glands and stroma separately as well as a total expression. We found that the maximum ER and PR expression was noted in the glandular epithelium, except for PR expression in the secretory phase which was more in the stromal cells than glandular epithelial cells, a finding supported by Press et al [12] Expression of these receptors was observed to be absent from vascular smooth muscle and endothelial cells in both endometrium and myometrium in the present study; also reported by Chakraborty et al, Press et al and Snijders et al [5,12,13] It was also noted during our study that the method of endometrial sampling did not affect the demonstration of ER and PR expression, a finding corroborated by study of Garcia et al [14] Antigen retrieval for ER is considered to be difficult as stated by Shet T et al, [15] but we did not find any significant discrepancy in the staining intensity for ER and PR. Although, staining for PR was more crisp and brighter than that for ER in most of our cases, which can be easily explained by the quantitative data from steroid-binding assays indicating that the content of PR in femtomoles per milligram cytosol protein is greater than ER.…”
Section: Discussionsupporting
confidence: 91%
“…A comparable distribution of patients in different age groups has been reported by Gleeson et al, Chakraborty et al and Chakravarthy et al [3,5,6] A few studies by Dhadhania et al and Gupta et al have however reported major number of patients from the age group of 41-50 yrs age group. [7,8] The literature reflects the sociocultural differences between Indian and western communities, as marriages occur earlier in India than western world.…”
Section: Discussionsupporting
confidence: 75%
“…15 Chakravarthy et al have emphasized importance of evidence based stepwise approach to managing cases of AUB while discussing their findings of markedly raised endometrial ER and PR in cases of simple and complex hyperplasia, mildly raised receptors in disordered proliferation and near normal receptor status in normal proliferation and irregular shedding. 16 Significant positive correlation was found between ER and PR in all phases of menstrual cycle in infertility and abnormal uterine bleeding. This can possibly be attributed to the high estrogen levels of the proliferative phase persisting in the late secretory phase in these cases.…”
Section: Discussionmentioning
confidence: 94%